Hyper-precarity and organization : the case of waste pickers in Istanbul - Terzi, Gülen Naz. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
This thesis discusses the waste pickers’ working and living conditions as well as their organizational experiences in Istanbul. In order to understand the organizational experiences, first of all, the living and working conditions of the waste pickers are discussed with the concept of hyper- precarity. Hyper-precarity has emerged as a result of the combination of the precarities created by the socio-legal status of waste pickers and their place in the labor market. The causes of hyper-precarity are the informalization created by the neoliberal capitalist system, the dispossession of peasants, forced displacement, transnational migration movements, and social and ethnic discrimination. People who live under hyper-precarity have to do jobs in informal sectors such as waste picking since they do not have any acceptable alternative. The commodification of garbage and the expansion of the recycling industry in Turkey has also increased the number of waste pickers. However, the commodification of garbage means a profit opportunity for international capitalists. Private companies, seeing the profitability in the recycling sector, want to monopolize waste management by cooperating with the state. This situation causes the waste pickers to be deprived of their job opportunities through state intervention and their hyper-precarity to deepen. Eliminating hyper-precarity has been the impetus for waste pickers' organization which aim to be treated as equal citizens and regain their livelihoods.
Keywords: Ragpickers -- Turkey -- İstanbul.; Salvage (Waste, etc.) -- Turkey -- İstanbul.; Ragpickers -- Employment -- Turkey -- İstanbul.; Hyper-precarity.